2009
DOI: 10.1177/1359105308097950
|View full text |Cite
|
Sign up to set email alerts
|

Social Representations of Female Orgasm

Abstract: This study examines women's social representations of female orgasm. Fifty semi-structured interviews were conducted with British women. The data were thematically analysed and compared with the content of female orgasm-related writing in two women's magazines over a 30-year period. The results indicate that orgasm is deemed the goal of sex with emphasis on its physiological dimension. However, the women and the magazines graft onto this scientifically driven representation the importance of relational and emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
1
43
0
2
Order By: Relevance
“…The meanings and experiences young (British) adults -women and mendescribe in relation to orgasm and sexual pleasure remain very similar to the experiences reported in previous qualitative research on orgasm. Orgasm is predominantly understood as an ultimate pleasure, and the 'goal' (and end) of sex, but also something that produces happiness, love, intimacy and closeness within relationships (Béjin, 1986;Fahs, 2011;Lavie & Willig, 2005;Lavie-Ajayi & Joffe, 2009;Nicholson & Burr, 2003;Potts, 2000). Our data show that our participants' experiences, the ways they interpret those experiences, and the meanings they attribute to orgasm and sexual pleasure, are already strongly socially-patterned, and are underpinned by dominant systems of meaning related to sex, heterosex and orgasm.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The meanings and experiences young (British) adults -women and mendescribe in relation to orgasm and sexual pleasure remain very similar to the experiences reported in previous qualitative research on orgasm. Orgasm is predominantly understood as an ultimate pleasure, and the 'goal' (and end) of sex, but also something that produces happiness, love, intimacy and closeness within relationships (Béjin, 1986;Fahs, 2011;Lavie & Willig, 2005;Lavie-Ajayi & Joffe, 2009;Nicholson & Burr, 2003;Potts, 2000). Our data show that our participants' experiences, the ways they interpret those experiences, and the meanings they attribute to orgasm and sexual pleasure, are already strongly socially-patterned, and are underpinned by dominant systems of meaning related to sex, heterosex and orgasm.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research into the experience and meaning of orgasm -typically focusing on women -has demonstrated complex and nuanced, yet patterned, meanings and experiences related to orgasm (e.g., Cacchione, 2007;Fahs, 2011;Hite, 2000;Lavie-Ajayi & Joffe, 2009;Nicholson & Burr, 2003;Potts, 2000). Given the sociocultural context noted above, orgasm has often unsurprisingly been identified as the peak sexual experience, the desired outcome (goal) of sex, the end and measure of successful sex (Lavie-Ajayi & Joffe, 2009;Potts, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations